Doctor Patient Communication: A Review - Begum, Tahmina (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Communication between patients and health professionals is seen as the core clinical function in building a therapeutic doctor-patient relationship, which is the heart and art of the medicine. Patients satisfaction is strongly influenced by the quality of the communication that occurs. Effective communication is the basis of mutual understanding and trust. This paper aims to raise awareness on the important issues involved in doctor-patient and inter-professional communication among the medical professionals. J Bangladesh Coll Phys Surg 2014; 32: 84-88